Addressing Sexual Dysfunction In Women With Psychiatric Disorders A Cross-Sectional Observational Study (Journal of Pharmaceutical Negative Results, 2021)
Background: It is a well-known fact that SD is common in women with psychiatric disorders but it is a problem that remains neglected. Objective: to identify the percentage of women with psychiatric disorders experiencing sexual dysfunction, the types of sexual dysfunction, and the effects on the woman and relationship, as well as the efficacy of different treatments. Study Design: A Cross-Sectional Observational Study. Duration and Place of the study: Department Of Psychiatry & Gynae & Obs Mardan Medical Complex (MMC) Mardan Between 8th May 2020 To 3rd Nov 2020. Material and Methods: Out of 105 female patients with different psychiatric disorders. About the control of variables, participants completed the Female Sexual Function Index (FSFI) and the Hamilton Rating Scale for Depression (HAM-D) and Anxiety (HAM-A). In addition, for gathering more elaborative sexual and psychiatric history a semi-structured interview was used. Patients were characterized based on symptoms of psychiatric disorders and data on sexual dysfunction were compared to these characteristics. Results: 105 female patients, with a mean age of 38.4 ± 10.2 years. The overall rate of sexual dysfunction in the participants was 68%, with a spectrum of manifestations. Decreased sexual desire (62%), sexual arousal disorders (54%), and orgasm disorders (48%). The results showed that out of all the factors, the severity of psychiatric symptoms had the most significant effect on sexual dysfunction (p<0.01).Conclusions: The present study found that female patients with psychiatric disorders have a high prevalence of sexual dysfunction and their level correlates with the degree of psychiatric symptoms.